2012
DOI: 10.1021/cs300043w
|View full text |Cite
|
Sign up to set email alerts
|

Gold-Containing and Gold-Generated 1,n-Dipoles as Useful Platforms toward Cycloadditions and Cyclizations

Abstract: Some of the most synthetically useful methods to construct molecular complexity include Diels−Alder, [1,3]-dipolar-and [m+n]-cycloadditions. In this context, the efficient generation of 1,n-dipoles plays a key role. Dipoles have been usually described as transient, difficult to harness species toward cycloaddition reactions. This review highlights the development of new methodologies for the efficient generation of these valuable intermediates by means of gold catalysis, and their application in the constructi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
43
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 198 publications
(43 citation statements)
references
References 96 publications
(124 reference statements)
0
43
0
Order By: Relevance
“…In contrast, known examples for water-induced product-divergence are relatively rare. 25,26 Recently, She et al successfully reported water-modulated cycloisomerization of the N-containing 1,6-or 1,7-enynyl esters, where (PPh 3 )AuSbF 6 , generated in situ from the mixture of AuClPPh 3 and AgSbF 6 , serves as the catalyst. 27 As shown in Scheme 1(1), when wet dichloromethane (DCM) is employed as the solvent, the reaction at ambient temperature evolves into bioactive pyrrolidines (n = 1) or piperidines (n = 2) as the hydrolysis products in good yields, whereas when dry DCM solvent is introduced under the same conditions (Scheme 1(2)), the hydrogenation products, dihydrofurans, are exclusively obtained in high yields.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, known examples for water-induced product-divergence are relatively rare. 25,26 Recently, She et al successfully reported water-modulated cycloisomerization of the N-containing 1,6-or 1,7-enynyl esters, where (PPh 3 )AuSbF 6 , generated in situ from the mixture of AuClPPh 3 and AgSbF 6 , serves as the catalyst. 27 As shown in Scheme 1(1), when wet dichloromethane (DCM) is employed as the solvent, the reaction at ambient temperature evolves into bioactive pyrrolidines (n = 1) or piperidines (n = 2) as the hydrolysis products in good yields, whereas when dry DCM solvent is introduced under the same conditions (Scheme 1(2)), the hydrogenation products, dihydrofurans, are exclusively obtained in high yields.…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, experimental and theoretical evidence supports the participation of one of those structures, but in many other cases the precise nature of these species remains unknown. The gold-activated allene complexes have been shown to participate in a great variety of intra- and intermolecular cycloaddition reactions, including [4 + 3], [4 + 2], [3 + 3], [3 + 2] or [2 + 2] annulation processes [1–10 2426]. Particular attention has been paid during the last years to the development of enantioselective versions of these processes by using chiral gold catalysts.…”
Section: Reviewmentioning
confidence: 99%
“…Especially relevant in terms of synthetic practicality are cycloadditions which are catalyzed by transition metal complexes [1923]. In particular, gold(I) complexes, owing to their high carbophilicity, low oxophilicity and high oxidation potential between gold(I) and gold(III) have shown a unique potential to unveil novel types of chemoselective and stereoselective cycloadditions involving alkynes, allenes or alkenes [2426]. …”
Section: Introductionmentioning
confidence: 99%
“…5 As expected these cationic species can demonstrate either carbene like 1,1-reactivity (cyclopropanation) or participate in vinylogous 1,3-functionalization reactions that have typically been associated with 1,3-dipoles. 6 In the context of the latter, Iwasawa 7 first invoked a gold-containing 1,3-dipole to prepare tricyclic indole derivatives in 2006. In 2008, we also proposed gold azomethine ylides as intermediates to understand the reaction of propargylic benzoates with α,β-unsaturated imines.…”
Section: Introductionmentioning
confidence: 99%